Global cassava strategy for the new millenium:CIAT's perspective - Ceballos, H. (International Center for Tropical Agriculture, 2001)
The economies of many Latin American countries have opened up to the global markets in recent years. These changes have had drastic effects on the agriculture of those countries. For instance, whereas Colombia did not import maize in 1990, ten years later it was importing more that 2 million tonnes per year. The same situation is true for many other tropical countries. As a result, agribusiness attention has recently focused on cassava as a source of raw material. In response to these changes in the markets, the CIAT cassava breeding project has directed its efforts to develop competitive cassava production for several different industries. The main goal is to increase yields and reduce costs. Dry matter yields as high as 15 t/ha have been obtained by combining outstanding germplasm with adequate agronomic practices. Dry matter productivity is the main goal for the development of these “industrial clones”. Other strategies for increasing yields and/or reducing production costs are mechanization of planting and harvesting, development of herbicide-resistance in cassava, improved fertilization techniques with animal manure, etc. The inclusion of cassava foliage in animal feed is also under analysis. Genetic transformation protocols are currently being fine-tuned so different desirable traits can be readily incorporated into elite cassava clones. The availability of molecular markers and a saturated genetic map will also contribute to an efficient selection of key traits in the breeding process. Sexual seeds from three large diallel crosses are currently being produced for genetic studies. The trials will be planted in the field early in 2001. In addition to producing a large segregating population, the study will allow us to better understand the genetics of the inheritance of several traits of agronomic value. The breeding scheme has been modified to speed up the selection process and to reach as soon as possible the stage of replicated trials. Collaborative research with IITA has been outlined to determine heterotic patterns between Latin American and African cassava gene pools. The germplasm bank collection is currently under evaluation for several traits of agronomic importance, including starch quality traits and vitamin content. There is an ongoing collaborative research project with the University of Bath (England) for elucidating the biochemical pathway leading to post-harvest physiological deterioration (PPD) of the roots. Parallel studies are underway to determine the genetic basis for reduced PPD, and sources of resistance have been identified (MDom 5 and MPer 183) and crossed with susceptible clones. In the area of integrated pest management an excellent source of resistance to whiteflies has been identified (MEcu 72) and antibiosis, as its mechanism of resistance, was determined. This genotype has been crossed with a susceptible clone and the segregating progeny is currently being analyzed for their reaction to the insect in the field; their molecular fingerprinting is also underway. ACMD (African Cassava Mosaic Disease) resistance will be incorporated into Latin American germplasm, using a recently identified molecular marker.